Superalkalis for the Activation of Carbon Dioxide: A Review - Srivastava, Harshita; Srivastava, Ambrish Kumar (Frontiers in Physics, 2022)
The activation of carbon dioxide is essential not only for global carbon balance but also for its conversion into fuel. As CO2 is highly stable, it is quite challenging to activate or reduce CO2. Recently, the ability of superalkalis to easily transfer an electron used to activate CO2 has been proposed in several studies. The superalkalis are species possessing lower ionization energy than alkali atoms. These are hypervalent species, having an excess of the electron. Owing to this, they possess strong reducing power and cause to bend the linear structure of CO2 by transferring an electron to it. Herein, we present a comprehensive account of the single-electron reduction and activation of CO2 by various kinds of superalkalis. This review also includes a novel strategy of the capture and storage of CO2 by superalkali.